CDC4 mutations occur in a subset of colorectal cancers but are not predicted to cause loss of function and are not associated with chromosomal instability. - Kemp, Z; Rowan, A; Chambers, W; Wortham, N; Halford, S; Sieber, O; Mortensen, N; von Herbay, A; Gunther, T; Ilyas, M; Tomlinson, I (2005)
CDC4/FBXW7 is part of a ubiquitin ligase complex which targets molecules such as cyclin E, c-myc, and c-jun for destruction. CDC4 mutations occur in several cancer types and are best described in colorectal tumors. Knockout of CDC4 in vitro in colorectal cancer cells causes changes suggestive of chromosomal instability (CIN). In p53(+/-) mice, radiation-induced lymphomas show deletion or mutation of one copy of CDC4 and knockdown of CDC4 leads to increased aneuploidy in mouse fibroblasts. We screened 244 colorectal tumors and 40 cell lines for CDC4 mutations and allelic loss. Six percent (18 of 284) of tumors, including near-diploid (CIN-) lesions, harbored CDC4 mutations and there was no association between mutation and CIN (polyploidy). The CDC4 mutation spectrum in colorectal tumors was heavily biased towards C:G > T:A changes, either missense mutations at critical arginine residues or nonsense changes in the 5' half of the gene. The reasons for this odd mutation spectrum were unclear but C:G > T:A changes were not found more often than expected at APC, K-ras, or p53 in the same tumors and we found no specific defects in DNA repair to account for the observations. No colorectal tumor was found to carry two CDC4 mutations predicted to abolish protein function; partial loss of CDC4 function may therefore cause tumorigenesis. The in vitro studies, therefore, did not assess the functional effects of mutant alleles which are found in vivo. CDC4 mutations may be selected primarily to drive progression through the cell cycle although CIN might be an important secondary effect in some cancers.